Effect of capecitabine on breast cancer patients with different estrogen receptor status - Gang Xu; Xin Lv; Ke Lu; Ming Hai Shen; Qing Hua Zhang; Wan Neng Pan (Bangladesh Pharmacological Society, 2020)
This meta-analysis is to compare the efficacy of capecitabine versus non-capecitabine chemotherapy on breast cancer patients with different estrogen receptor (ER) status. We searched relevant literatures from EMBASE, PubMed and OVID library to analyze pathologic complete response rate (PCR), overall survival (OS), disease-free survival (DFS), progression-free survival (PFS), and time to disease progression (TTP). Eleven different studies were enrolled, which revealed that ER positive breast cancer patients who received treatment regimen containing capecitabine can effectively improve PFS, PCR, TTP. However, the difference between capecitabine-containing and non-capecitabine group has no significant for DFS, OS. ER negative breast cancer patients who received treatment regimen containing capecitabine can obviously improve DFS and TTP. However, there was no significant effect for PFS, PCR and OS. The results indicated that capecitabine in combination with other chemotherapy drugs for breast cancer is effective, which can delay the progression time in patients to some extent.